Hidden Desires and Social Norms in 'Young Goodman Brown': A Psychoanalytic Analysis - Salsabila Rizqi Sanina Amisar; Teguh Kasprabowo (Faculty of Language and Literature, University of Surakarta, 2024)
Literature has provided a deep understanding of the human psyche and behavior. “Young Goodman Brown” by Nathaniel Hawthorne is a literary work exploring the psychological component. This study attempts to discover the conflict between hidden desires and social norms and the anxieties and fears from a psychoanalysis point of view. This study uses qualitative descriptive techniques to delve into the context. In addition, this study uses Freudian Psychoanalytic which are Id, Ego, and Superego. The research contributes to the broader field of literary analysis related to psychoanalytic theory, facilitating a deeper understanding of the story by revealing the character’s actions. By focusing on the protagonist’s personality traits, readers are expected to gain a comprehensive understanding of the story's central conflict. This study is intended to engage scholars, researchers, and students in the interpretive analysis of this short story.